2017
DOI: 10.1016/j.virusres.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of host immune defenses by human papillomavirus

Abstract: A majority of human papillomavirus (HPV) infections are asymptomatic and self-resolving in the absence of medical interventions. Various innate and adaptive immune responses, as well as physical barriers, have been implicated in controlling early HPV infections. However, if HPV overcomes these host immune defenses and establishes persistence in basal keratinocytes, it becomes very difficult for the host to eliminate the infection. The HPV oncoproteins E5, E6, and E7 are important in regulating host immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 182 publications
(212 reference statements)
1
138
0
7
Order By: Relevance
“…Persistent and severe papillomatosis, features of our cases, are often associated with immunodeficiency, immunosuppression and/or viral virulence factors . Contact horses, including immature horses at a breeding facility, did not develop similar papillomatosis, which further suggested altered individual immune function.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Persistent and severe papillomatosis, features of our cases, are often associated with immunodeficiency, immunosuppression and/or viral virulence factors . Contact horses, including immature horses at a breeding facility, did not develop similar papillomatosis, which further suggested altered individual immune function.…”
Section: Discussionmentioning
confidence: 54%
“…EcPV8‐associated papillomas were epithelial plaque type, as occurs with genital papillomas and auricular plaques . Hyperkeratosis was common, similar to auricular plaques, but unlike genital papillomas, where it is usually not a feature but rarely it is pronounced .…”
Section: Discussionmentioning
confidence: 99%
“…E7 has been shown to directly block the MHC‐I heavy chain promoter . HLA‐A and ‐B can be retained by an HPV16 E5‐mediated mechanism within the cell . On the contrary, HLA‐C and HLA‐E are not influenced by E5.…”
Section: Antigen Processingmentioning
confidence: 99%
“…In addition, since the reactivation would appear a long time after the infection, it is plausible to assume that no specific tests targeting oncoviruses would be implemented and the presence of the integrants might remain undetected. The immune response, in particular the action of interferon, is able to deplete viral episomes from the infected cells [86]; however integrants cannot be removed by this mechanism and can therefore persist after viral clearance. Interestingly, it has been reported that interferon can facilitate viral integration [87].…”
Section: 2217/fvl-2017-0063mentioning
confidence: 99%